2013
DOI: 10.1007/s00411-013-0494-5
|View full text |Cite
|
Sign up to set email alerts
|

Radio-sensitization of human leukaemic MOLT-4 cells by DNA-dependent protein kinase inhibitor, NU7441

Abstract: We studied the effect of pre-incubation with NU7441, a specific inhibitor of DNA-dependent protein kinase (DNA-PK), on molecular mechanisms triggered by ionizing radiation (IR). The experimental design involved four groups of human T-lymphocyte leukaemic MOLT-4 cells: control, NU7441-treated (1 μM), IR-treated (1 Gy), and combination of NU7441 and IR. We used flow cytometry for apoptosis assessment, Western blotting and ELISA for detection of proteins involved in DNA repair signalling and epifluorescence micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 31 publications
0
12
1
Order By: Relevance
“…On the other hand, it significantly increased radiation-induced cytotoxicity and genotoxicity, indicating no direct relation between early H2AX phosphorylation and DNA damage repair capacity in human peripheral lymphocytes. Our results and data reported by others show NU7441 to be a potent radiosensitizing agent (Song et al, 2013;Ciszewski et al, 2014;Tichy et al, 2014). However, lymphocytes and highly differentiated (G 0/ G 1 ) tissues might be significantly affected by its non-selective action.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…On the other hand, it significantly increased radiation-induced cytotoxicity and genotoxicity, indicating no direct relation between early H2AX phosphorylation and DNA damage repair capacity in human peripheral lymphocytes. Our results and data reported by others show NU7441 to be a potent radiosensitizing agent (Song et al, 2013;Ciszewski et al, 2014;Tichy et al, 2014). However, lymphocytes and highly differentiated (G 0/ G 1 ) tissues might be significantly affected by its non-selective action.…”
Section: Discussioncontrasting
confidence: 55%
“…NU7441 has not yet been used in oncological therapy. However, in vitro studies have demonstrated its ability to enhance the cytotoxicity of IR in cancer cell lines while expressing low toxicity in vivo, which validates this substance for further testing (Nutley et al, 2005;Zhao et al, 2006;Yu et al, 2012;Tichy et al, 2014). Another PI3-K inhibitor is KU55933.…”
Section: Introductionmentioning
confidence: 90%
“…NU7441, a derivative from LY294002, is a synthetic and specific DNA-PK inhibitor. In in vitro experiments, NU7441 exerted radiosensitizing activity in breast cancer, leukemia, and prostate cancer [15][16][17]. However, no studies have been performed to examine the effect of NU7441 on liver cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…1A). Significantly, two DNA-PKcs inhibitors, NU7026 [21] and NU7441 [22], remarkably enhanced WAY-600-mediated activity, resulting in dramatic HT-29 cell death (Fig. 1A).…”
Section: Dna-pkcs Inhibitors Potentiate Way-600-induced Cytotoxicity mentioning
confidence: 95%